Propuesta de Restructuración de los Procesos Logísticos de Aprovisionamiento en Empresa Solmaq de la Costa S.A.S, en Barranquilla Colombia. - Rodríguez Rangel, Andreína Micheld; Yaneth González, Yohandri Liseth (Universidad Antonio Nariño, 2022)
Today one of the most important factors in the business world is the development of internal logistics based on technological tools, which help improve processes within the supply chain, this in order to generate a more fast and efficient for the distribution of products on time, and with less cost. The business economic sector has undergone many changes since the increase in competencies, even the globalization and internationalization of the economy, but it is the logistics one of the most necessary strategies to carry out the organization of a company, especially in supply, storage and distribution, these being the most important elements of business logistics. Supply in companies is essential to increase its competitiveness in a market in which there are more and more competing companies and in which the demand of the clients is increasing. The The importance of logistics in companies today lies in the fact of being able to supply of raw materials and products in a short period of time, so that the final product can be made available to the consumer as soon as possible. For this it is done completely good inventory management is essential, so that situations do not occur of shortage. In order to be more and more efficient, logistics is carrying out a technification process and increasingly depends on new technologies. Colombia, presents a score of 2.94 out of 5 in the Logistics Performance Index to date, so far in 2021 there has been an increase in employment of 3,465 people with respect to previous years, which represents a growth in employment in this sector of 33,720 people, and 3.7%. 64% of companies in Colombia do not use any technological tool in its logistics processes. Currently, this creates difficulty in compliance with delivery times. That is why the company SOLMAQ DE LA COSTA